FACTORS THAT INFLUENCE DEMAND FOR SHARIA FINANCING ON CHANGES IN MSME INCOME IN SUMBAWA DISTRICT : (Case Study on Customers of Bank Syariah Indonesia Sumbawa District Branch) - Nuryani, Hanifa Sri (STIE Mahardhika, 2024)
This research aims to determine the factors that influence the demand for sharia financing on increasing MSME income in Sumbawa District (case study of customers of Bank Syariah Indonesia, Sumbawa Regency Branch). The research results are: first, the impact of Bank Syariah Indonesia's sharia system in Sumbawa District shows a significant influence on changes in income of micro, small and medium enterprises (0.000 < 0.05). The factor that causes this is that small and medium micro business actors in Sumbawa District realize that the sharia system will always bring blessings to every business they undertake. Second, the effect of promotion on changes in income of micro, small and medium enterprises in Sumbawa District in the case of Bank Syariah Indonesia in Sumbawa District did not have a significant impact (0.571 > 0.05). The cause of this is that micro, small and medium business actors in Sumbawa District cannot access the internet, in fact the internet network in some places for small, micro and medium business actors is not yet accessible, where promotion of financing products is mostly done online. Third, the influence of trust in Bank Syariah Indonesia, Sumbawa District Branch, has a positive impact on changes in the income of micro, small and medium enterprises (0.006 < 0.05). The factor that causes this is that micro, small and medium enterprises already believe in the systems and products offered by Bank Syariah Indonesia, Sumbawa District Branch, so that the bank and micro, small and medium enterprises are always on time in repaying their loans every month. Fourth, the influence of facilities and services on demand for sharia financing at Bank Syariah Indonesia Sumbawa District Branch for micro, small and medium enterprises does not have a significant impact (0.909 > 0.05). The factor that causes this is the lack of supporting capacity of human resources.